Comparison of FACTS STATCOM models for damping oscillations in power system due to small perturbations - Petean-Pina, A. [UNESP]; Dearaujo, P. B. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents small-signal stability studies of a multimachine power system, considering Static Synchronous Compensators (STATCOM)and discussed control modes of the STATCOM. The Power Sensitivity Model(PSM)is used to represent the electric power system. The study is based on modal analysis and time domain simulations. The results obtained allow concluding that the STATCOM improves the stabilization in the electric power system. © 2011 IEEE.
Keywords: Electric Power System; Power Sensitivity Model; Static Synchronous Compensators (STATCOM); Control modes; Damping oscillation; Multi machine power system; Power sensitivity; Power systems; Small perturbations; Small signal stability; Statcom; Static synchronous compensator; Time-domain simulations; Angle measurement; Control system stability; Electric power transmission; Electricity; Modal analysis; Power transmission; Time domain analysis; Synchronous machinery